Molecular Dynamics Investigation on Adsorption Layer of Alcohols at the Air/Brine Interface - Nguyen, Van Cuong; Phan, Chi; Ang, Ming; Nakahara, H.; Shibata, O.; Moroi, Y. (American Chemical Society, 2015)
Alcohols are a significant group of surfactants which have been employed extensively in industry to improve the interfacial effects. Recently, the change in surface potential (ΔV)of two isomeric hexanols, methyl isobutyl carbinol (MIBC) and 1-hexanol, was investigated by using an ionizing241Am electrode. It clearly showed the opposite effects between MIBC and 1-hexanol in the interfacial zone: one enhanced the presence of cations, whereas the other enhanced the presence of anions. This study employs molecular dynamics simulation to provide new insights into the interactions between alcohol molecules and ions as well as water at the molecular level. The results qualitatively agreed with the experimental data and verified the significance of MIBC branching structure on the molecular arrangement within the interfacial zone. The results also highlighted the role of the second water layer on the interfacial properties.